Demon slayer = Kimetsu no yaiba. Volume 1, Cruelty - Gotoge, Koyoharu, 1988-; Stan!, 1964- (VIZ Media, LLC, 2018)
In Taisho-era Japan, Tanjiro Kamado is a kindhearted boy who makes a living selling charcoal until his peaceful life is shattered when a demon slaughters his family and turns his sister into another demon, forcing Tanjiro on a dangerous journey to destroy the demon and save his sister.